Nghiên cứu áp dụng công nghệ mới vào sản xuất vải dệt chất lượng cao đáp ứng yêu cầu xuất khẩu - Mai, Hoàng Ân. S (2011)
Tác giả: Mai Hoàng Ân. S; Nguyễn Văn Thông, TS; Nguyễn Tiến Dũng, KS; Nguyễn Sỹ Phương, ThS; Nguyễn Kim Thanh, KS -- Từ khóa: Công nghệ mới; Dệt vải